The Influence of Principals’ Managerial Competence, Madrasah Culture, and Teachers’ Work Discipline on the Quality of Islamic Primary Schools - Farah Amalia; Senowarsito Senowarsito; Harto Nuroso; Aditi Verma (Yayasan Adra Karima Hubbi, 2026)
Background. The quality of Madrasah Ibtidaiyah is a crucial indicator of the effectiveness of Islamic basic education in producing academically competent students with strong character. Improving madrasah quality requires the optimization of internal organizational factors, particularly managerial leadership, institutional culture, and teacher professionalism. However, variations in educational outcomes across madrasahs indicate that these factors may not contribute equally to institutional performance. Purpose. This study aims to examine the influence of principals’ managerial competence, madrasah culture, and teachers’ work discipline on the quality of Madrasah Ibtidaiyah in Guntur District, Demak Regency, both partially and simultaneously. Method. This research employed a quantitative ex post facto correlational design. The population consisted of 141 teachers and principals, with a sample of 105 respondents selected using proportional random sampling. Data were collected through Likert-scale questionnaires and analyzed using descriptive statistics and multiple linear regression, preceded by tests of validity, reliability, and classical assumptions. Results. The findings revealed that all variables were in the good to very good category. Teachers’ work discipline had the strongest positive and significant effect on madrasah quality, followed by madrasah culture. Principals’ managerial competence did not show a significant partial effect when tested simultaneously with other variables. However, the three independent variables together significantly influenced madrasah quality, with a coefficient of determination of 0.908, indicating that 90.8% of the variance in quality could be explained by the model. Conclusion. The quality of Madrasah Ibtidaiyah is primarily determined by operational factors directly related to teaching practice, especially teacher discipline and institutional culture, while managerial competence functions as a supporting factor that shapes the organizational environment. Improving madrasah quality therefore requires an integrated approach focusing on strengthening professional discipline, positive organizational culture, and effective leadership.